The World seen by Hungarian students: a mental map analysis - Rédei, Mária; Kincses, Áron; Jakobi, Ákos (Hungarian Geographical Bulletin, 2011)
The project “Eurobroadmap”, funded by the European Commission, is setting out a worldwide survey of the opinions of undergraduate students in diff erent fi elds of learning (geography, political science, management, medicine and arts) in order to analyze their perception of the World and Europe. Its objective is to catch how undergraduate students from different domains and from different countries perceive the contemporary World in general and Europe in particular.More precisely, the project focuses on two aspects of this vision: attractive and repulsive places, and relevant partitions of the World. The objectives were reduced to 10,320 questionnaires in 18 countries and 43 cities all around the world. Hungary participated in the survey by 244 questionnaires. The article gives an overview on global and local level on the valuable considerations of the Hungarian students’ cognitive geographical perceptions.